2020
DOI: 10.1017/s1049023x2000134x
|View full text |Cite
|
Sign up to set email alerts
|

Use of In Situ Simulation to Improve Emergency Department Readiness for the COVID-19 Pandemic

Abstract: Introduction: During the world-wide coronavirus disease 2019 (COVID-19) outbreak, there is an urgent need to rapidly increase the readiness of hospitals. Emergency departments (EDs) are at high risk of facing unusual situations and need to prepare extensively in order to minimize risks to health care providers (HCPs) and patients. In situ simulation is a well-known method used in training to detect system gaps that could threaten safety. Study Objectives: One objective is to identify gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…The role of simulation-based drills in the medical field is well established. These drills provide an opportunity for HCWs to rehearse high-risk procedures such as ETI for COVID-19 patients under real-world conditions [ 19 , 20 ]. They also enable HCWs to better understand their roles and responsibilities, improve communication among team members, and increase teamwork competencies while performing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The role of simulation-based drills in the medical field is well established. These drills provide an opportunity for HCWs to rehearse high-risk procedures such as ETI for COVID-19 patients under real-world conditions [ 19 , 20 ]. They also enable HCWs to better understand their roles and responsibilities, improve communication among team members, and increase teamwork competencies while performing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…2 55-57 We observed that even though the included studies were quite recent, as ISS seems to have emerged in the last 20 years, the vast majority used observational prospective designs. With ISS, the proximity between the intervention and the possible patient-centred outcomes is inspiring and educators should seek collaboration with methodologists to elaborate research protocols leaning Kirkpatrick level n (%) References KP4: patient outcome 22 Abulebda et al 29 Aljahany et al 76 Barni et al 112 Chan et al 31 Couto et al 36 Geis et al 72 Gray et al 42 Hamman et al 59 Hamman et al 60 Hargestam et al 61 Kerner RL et al 62 Kobayashi et al 63 Lavelle et al 113 Paltved et al 32 Patterson et al 10 Shah et al 37 Shrestha et al 34 Steinemann et al 40 Wang et al 114 Whitfill et al 69 Petrosoniak et al 75 Theilen et al 41 Walsh et al 68 KP5: costs 2 Theilen et al 41 Petrosoniak et al 75 Other, NA 10 Hunt et al 44 Kobayashi et al 52 Mondrup et al 33 Kessler et al 115 Siegel et al 43 Stevens et al 116 Wieck et al 117 Nadkarni et al 118 Auerbach et al 119 O'Leary et al 87 NA, not available.…”
Section: Study Methodology Limitationsmentioning
confidence: 99%
“…A survey 23 carried out in an emergency service, with a multidisciplinary team, assessed by simulation the basic and advanced skills for establishing airways in patients infected with COVID-19. Although most professionals perform the procedures correctly, about 21% did not follow the correct sequence and procedure for the use of personal protective equipment and hand hygiene.…”
Section: Discussionmentioning
confidence: 99%